Efektivitas Buah Stroberi Terhadap Bakteri Streptococcus mutans Penyebab Karies Gigi di dalam Rongga Mulut - R Ardian Priyambodo; Aurelia Tifany (Poltekkes Kemenkes Makassar, 2018)
Strawberry is one of the most popular fruits because of its color and shape is very small. Strawberry have long been known as herbs that have health benefits because they contain antibacterial xylitol. Xylitol is believed to reduce plaque on the teeth by inhibiting streptococcus mutans bacteria.This study aims to test the effectiveness of strawberries against streptococcus mutans bacteria that cause dental caries in the oral cavity. This research is an experimental research by taking respondents as much as 5 respondents with diffusion method. Data analysis used in this research use SPSS 24.0 by using T test before and after. The results of this study indicate that strawberry fruit is effective in reducing the bacteria streptococcus mutans cause caries in the oral cavity, it is obtained value pValue = 0,002 (Pvalue <0,05).For the next researcher is suggested to do the isolation of xylitol compound in order to get maximum result, it is also suggested to do the test about xylitol level and making formulation of mouthwash from strawberry extract.Keywords: Antibacterial Activity and Streptococcus Mutans.